FORMY PRZYSTOSOWANIA MŁODZIEŻY W RODZINIE Z PROBLEMEM ALKOHOLOWYM - Niewiadomska, Iwona; Fel, Stanisław (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The article presents the results of research on ways to adapt youth, who are brought up in families with alcohol problems. The research was conducted on a group of 553 people. The RISB Sentence Completion Test by J. Rotter was used to determine the forms of adaptation. Statistical calculations were performed using cluster analysis. On the basis of the analyses, four types of adaptation were identified in individuals, who were brought up in families with alcohol problems: 1) high adaption, due to the lack of problems in such dimensions as; extra-family interpersonal relationships, family contacts, their relationship to themselves, the sense of accomplishing personal aspirations, experiencing psychological problems and implementing pro-social values; 2) average potential adaptation – mainly due to disturbances in the sphere of family relations; 3) age adaptation – primarily because of the greater intensity of psychological and interpersonal problems; 4) low adaptation, due to the high level of problems in areas such as; extra-family interpersonal relationships, family contacts, their relationship to themselves, the sense of accomplishing personal aspirations, experiencing psychological problems and implementing pro-social values.